The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1002/jnr.490390309
|View full text |Cite
|
Sign up to set email alerts
|

Normal distribution of alpha 2‐adrenoceptors in the rat spinal cord and its modification after noradrenergic denervation: A quantitative autoradiographic study

Abstract: The distribution of alpha 2 (alpha 2)-adrenoceptors along cervical, thoracic, lumbar, and sacral segments of the spinal cord of normal rats has been studied by quantitative autoradiography using the specific alpha 2-antagonist [3H]rauwolscine as a ligand. In addition, the influence of noradrenergic (NA) denervation [obtained either by complete transection of the spinal cord at vertebrae level T8-T9 or by selective lesion of NA spinal cord system carried out by intracisternal injection of 6-hydroxydopamine (6-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 46 publications
2
41
0
Order By: Relevance
“…There are consistent reports of small amounts of residual NA that persists in the spinal cord after SCI (Magnusson 1973;Roudet et al 1993Roudet et al , 1994, although the origin of this NA remains a matter of dispute. Based on biochemical methods to visualize catecholamines in the spinal cord, McNicholas et al (1980) suggested that this residual NA after SCI arises from small sympathetic efferents branching off of blood vessels in the spinal cord.…”
Section: Possible Peripheral Source Of Na After Spinal Cord Injurymentioning
confidence: 83%
See 1 more Smart Citation
“…There are consistent reports of small amounts of residual NA that persists in the spinal cord after SCI (Magnusson 1973;Roudet et al 1993Roudet et al , 1994, although the origin of this NA remains a matter of dispute. Based on biochemical methods to visualize catecholamines in the spinal cord, McNicholas et al (1980) suggested that this residual NA after SCI arises from small sympathetic efferents branching off of blood vessels in the spinal cord.…”
Section: Possible Peripheral Source Of Na After Spinal Cord Injurymentioning
confidence: 83%
“…Indeed, previous studies have shown that ␣ 2 receptors on motoneurons induce a hyperpolarization by blocking I h currents (Adachi et al 2005;Parkis and Berger 1997;Rekling et al 2000), and such I h currents contribute ϩ10 mV to the resting potential in our chronic spinal rats ). Furthermore, ␣ 2 receptor expression can be detected throughout the spinal cord with the highest densities in the superficial dorsal horn and moderate densities in the portion of be ventral horn containing motoneurons (Giroux et al 1999;Roudet et al 1994). All together, ␣ 2 receptor agonists like clonidine or tizanidine are likely to produce their antispastic action primarily by inhibiting afferent transmission to motoneurons and secondarily by hyperpolarizing motoneurons, making motoneurons less likely to be activated during a muscle spasm.…”
Section: ␣ 2 Receptors Inhibit Epsps But Not Picsmentioning
confidence: 99%
“…However, preliminary unpublished data in spinal cats indicate that 30 days following spinalization, alpha2-noradrenergic receptors are upregulated in segments L3-L5 (lamina II, III, V, and X) and down-regulated from L6 or L7 to S3 segments (lamina II, III, V, VI, VII, and X), suggesting the importance of these receptors in midlumbar segments in the expression of spinal locomotion (Chau et al 2000). In intact rats, alpha2-noradrenergic receptors were correlated with the distribution of NA terminals and were found at all rostrocaudal levels of the spinal cord throughout the whole gray matter with a preferential location in the superficial dorsal horn (Roudet et al 1994). …”
Section: Noradrenergic Mechanismmentioning
confidence: 98%
“…At the spinal level, the ␣ 2 -adrenoceptor is present presynaptically at the primary afferent terminals and postsynaptically on dorsal horn neurons. Although the ␣ 2A -adrenoceptor subtype is located predominantly on the terminals of primary afferents (Sullivan et al, 1987;Roudet et al, 1994;Stone et al, 1998;Overland et al, 2009;Riedl et al, 2009), the ␣ 2C -adrenoceptor subtype is present mainly on spinal dorsal horn neurons (Stone et al, 1998). Stimulation of ␣ 2 -adrenoceptors with clonidine dose-depend-ently reduces excitation of dorsal horn neurons evoked by primary afferent stimulation (Sullivan et al, 1987).…”
Section: Introductionmentioning
confidence: 99%